Analysis of tool wear and hole quality during Ultrasonic Assisted Drilling (UAD) of Carbon Fibre Composite (CFC)/titanium alloy (Ti6Al4V) stacks - Dahnel, Aishah Najiah; Barnes, Stuart; Ascroft, Helen; Gloger, Maximilian (American Society of Mechanical Engineers (ASME), 2015)
Carbon Fibre Composite (CFC) and titanium (Ti) alloys have been widely employed in the aerospace industry due to their high strength to weight ratios. For making a military aircraft body, these materials are usually stacked together with titanium alloys serving as the airframe, while CFC is the outer skin. Drilling is often performed in one shot from the CFC outer skin through to the titanium alloy airframe for the purpose of assembling them by mechanical means using rivets, screws, nuts and bolts. Conventional drilling of these CFC/Ti stacks, however, often results in two major issues; rapid tool failure and poor hole quality. This paper considers the potential of employing Ultrasonic Assisted Drilling (UAD) on stack materials in order to improve tool life and hole quality. Experiments comparing conventional drilling and UAD on CFC/Ti6Al4V stack using reground 6.121 mm-diameter TiAlN coated tungsten carbide twist drills are presented. Reground drills were used by way of replicating typical current practice in industry. A constant cutting speed and feed rate of 50 m/min and 0.05 mm/rev, respectively was used in both experiments. During UAD experiments, ultrasonic amplitude and frequency was fixed at 2.6 µm and 42.7 kHz, respectively. A total of 100 holes were drilled in the stacks during each drilling processes (conventional drilling and UAD). Machinability was assessed in terms of thrust forces, tool wear, hole diameter, CFC delamination and titanium burr. Thrust forces were measured using a dynamometer; tool wear was examined using an optical microscope and a Scanning Electron Microscope (SEM); and holes diameter were measured using a bore micrometer. Hole defects; CFC entry delamination was examined and quantified using an optical microscope, while titanium exit burr were investigated using both an optical microscope and a depth gauge. The dominant types of tool wear during drilling of CFC/Ti6Al4V stacks were caused by titanium adhesion/fusion on the cutting edges. In addition, abrasive wear caused by abrading carbon fibres against cutting edges were also observed. Poor hole quality of the stacks included inconsistent diameter of CFC and titanium holes; CFC delamination at the hole entrance and burr formation as the drill exited the titanium. The difference in thrust forces produced by conventional drilling and UAD were minor. It was observed that UAD resulted in less tool wear rate and a reduction of adhered titanium alloy on the cutting edges, more consistent hole diameters and less titanium burr compared to conventional drilling. However, larger CFC delamination was observed during UAD than conventional drilling.